Effect of Dietary Supplementation with Sources of Omega-3 and Omega-6 Fatty Acids on Certain Blood Characteristics of Laying Quail - Al-Daraji, Hazim J.; Al-Hassani, Ali S.; Al-Mashadani, H.A.; Al-Hayani, W.K.; Mirza, H.A. (International Journal of Poultry Science, 2010)
The objective of this experiment was to determine the effects of dietary supplementation with different fat sources on blood parameters of Japanese quail (Coturnix coturnix japonica). Eighty four 7-week old laying quail were randomly assigned to 4 treatment groups (21 birds per group) with 3 replicates for each treatment group and fed for three months on a commercial diet supplemented with 3% of either sunflower oil (T1), flax oil (T2), corn oil (T3) or fish oil (T4). The birds received water and feed ad libitum during the experiment. During the last month of experiment blood samples were collected fortnightly from each bird. The first blood samples collection was used to determine fresh blood parameters, while the second blood samples collection was used after pooled blood samples for each replicate of treatment group to determine serum chemistry traits. Dietary supplementation with 3% fish oil (T4) caused a significant (p